Synthesis and Characterization of New Mesomorphic Azo Compounds and Study their Photoluminesecence Properties (Baghdad Science Journal, 2016)
The preparation of a new Azo compounds of highly conjugated dimeric and polymeric liquid crystal to achieve the crystalline characteristics Which have structures assigned based on elemental analysis, IR 1HNMR and CHNS-O while mesogenic properties have been set for DSC and hot-stage polarizing optical microscopy. The compounds show enantiotropicnematic phase being displayed.The compounds show photoluminescence properties in the organic solution at room temperature, with the fluorescence band centered around 400 nm.